Idioms Analysis In The Coldplay Songs Entitled Hymn For The Weekend, Amazing Day, A Head Full Of Dreams, and Birds - arini hidayah (JELLE : Journal Of English Literature, Linguistics, and Education, 2022)
This research aims to analyze the types of idioms and the meaning of idioms in Coldplay's song, entitled Hymn For The Weekend, Amazing Day, A Head Full Of Dreams, And Birds by using F R Palmers theory of idiom types and Geoffrey Leech's theory of idiom meanings. This research is a qualitative descriptive research. The data of this research are Coldplay song lyrics. Data analysis was carried out by categorizing all lyrics into types of idioms and idiom meanings. These types are analyzed to find out what meanings are in the song lyrics. Research used document analysis to obtain data. In analyzing the data, the research used New Criticism. In validating the data, the research used triangulation theory.The research found that the researchers found 176 of the four song lyrics. The data are classified into idiom meanings which consist of Conceptual Meaning (1 data), Connotative Meaning (22 data), Stylistic Meaning (24 data), Affective Meaning (84 data), Reflective Meaning (15 data), Collocative Meaning (1 data) , Thematic Meaning (28 data). Then the researchers also clarifies into idiom types which consist of phrasal verb (11 data), preposition verb (10 data), partial idiom (8 data) of the data, Affective and Phrasal verb meanings are more dominant than other types. This describes the speaker expressing more personal feelings or emotions and using verbs with adverbs.